I wonder why stars twinkle : and other questions about space - Stott, Carole (Danbury, Connecticut : Grolier Inc, 1999)
With information and quirky facts to explain everything from 'How many starts are there?' to 'How hot is the Sun?'.
Includes index
Keywords: Science